2016
DOI: 10.2146/ajhp150273
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P–450 gene and drug interaction analysis in patients referred for pharmacogenetic testing

Abstract: In a mixed-race population of over 20,000 U.S. patients, CYP gene polymorphisms associated with DDIs and other interaction threats were prevalent, and most individuals were not categorized as normal metabolizers of all five CYP isozymes of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…51 Similarly, in a study published in 2016, researchers identified that 69.1% of 20,534 patients had at least 1 reported drug interaction and, of those interactions determined to be severe, 24.6% were DGIs. 52 Collectively, these data indicate that genetic variations can substantially contribute to MRPs among older adults. These results are clinically important because genetically determined interindividual differences in drug disposition and response can affect clinical outcomes in older adults, whom are more susceptible to therapeutic failures and adverse drug reactions.…”
Section: Discussionmentioning
confidence: 88%
“…51 Similarly, in a study published in 2016, researchers identified that 69.1% of 20,534 patients had at least 1 reported drug interaction and, of those interactions determined to be severe, 24.6% were DGIs. 52 Collectively, these data indicate that genetic variations can substantially contribute to MRPs among older adults. These results are clinically important because genetically determined interindividual differences in drug disposition and response can affect clinical outcomes in older adults, whom are more susceptible to therapeutic failures and adverse drug reactions.…”
Section: Discussionmentioning
confidence: 88%
“…Although not discussed in detail in this review, it is important to consider the role of pharmacogenomics in determining the magnitude of drug‐drug interactions and drug‐drug‐gene interactions—that is, polymorphisms in a metabolic pathway and inhibition or induction of the same or minor pathway . In fact, a cross‐sectional study involving 22,885 patients found that there were approximately 6,900 drug interactions, of which drug‐drug‐gene, drug‐gene, and drug‐drug interactions accounted for 22%, 25%, and 53%, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…These comments may be based on analysis of a single gene at a time or in combination. The interpretative report might include comments on a single medication, multiple medications, or a disease‐specific set of medications (e.g., cardiology panel) . Disease‐specific medication set reports may not cover the complete clinical importance of the results if the results applied to medications in multiple clinical areas.…”
Section: Reporting Of Resultsmentioning
confidence: 99%